Online interprofessional education for in-service health-care providers improved HIV performance indicators at health facilities in Uganda: a targeted training approach - Isaac Derick Kimera, MBChB; Shardrack Wanyina, MSc; Martin Muddu, MMed; Denis Bwayo, MMed; Eleanor Namusoke-Magongo, MMed; Nelson K Sewankambo, ProfMMed; Fred Collins Semitala, MMed (Elsevier, 2022)
Background: The Makerere University Education for Interprofessional HIV Service Delivery in Uganda capacity-building programme provides online, in-service interprofessional education to HIV health-care providers through a case-based approach. We used this training to address suboptimal performance among health-care providers. Methods: We used a multilayered integrated training and impact assessment on HIV health outcomes. In partnership with a Ugandan organisation implementing the US President's Emergency Plan for AIDS Relief, we identified health facilities underperforming on selected HIV programme indicators: pre-exposure retention at 12 months for key populations and viral load suppression and annual retention for key populations, which could be aligned with the training modules. We selected health-care providers committed to completing the interprofessional education training and application of interprofessional practice at their workstations from five health facilities. Selected health-care providers were enrolled for the Makerere University Education for Interprofessional HIV Service Delivery in Uganda online training programme. Findings: Of the health-care providers enrolled (n=55), 32 (58%) were women; 17 (31%) were nurses; 9 (16%) were clinical officers; 8 (15%) were counsellors; 6 (11%) were medical officers; 5 (9%) were data clerks; 4 (7%) were laboratory personnel; and 6 (11%) included social workers, records officers, and dispensers. 45 (82%) health-care providers completed the training, and four of the five health facilities initiated quality improvement projects aligned with baseline indicators. The percentage of pre-exposure retention at 12 months improved from 4% to 80%; the percentage of viral load coverage for key populations improved from 50% to 94%; the percentage of viral load suppression improved from 80% to 96%; and the percentage of annual retention for key populations improved from 63% to 85%. Interpretation: In-service and online interprofessional education training, interprofessional practice mentorship, and continuous quality improvement for HIV care improved HIV programme indicators. A multilevel stakeholder engagement strategy was associated with strengthened training and enhanced potential for sustainability and impact on patient outcomes. Funding: Human Resources Services Administration through award 6U1NHA31422-02-04 to University of California San Francisco and African Forum for Research and Education in Health.